Information System Web Of Sciences: Mirror Or Tool? - Didenko, Yu.V.; Radchenko, A.I.; Koval, N.V. (Science and Innovation, 2024)
The degree of presence and «visibility» of scientific articles of Ukrainian scientists in the database Web of Sciences Core Collection is briefly described. Survey is conducted for the category «scientific article» in the category «Ukraine». The focus is on the 1991-2016 period. The main causes of low «visibility» of national publications in this database are determined. Initial steps to address the problems are proposed.